Optimization Research of the Hinge Position and Output Speed of Electromechanical Erection Device - Wei Cai; Shangjun Ma; Jianxin Zhang; Yong Zhou; Xiang Chen; Geng Liu (Jixie chuandong, 2021)
In order to realize the fast erection of electromechanical actuator， and the influence rule of the hinge position and output speed on output power and force in erection device is revealed， the hinge position and the output speed of the system are optimized and researched. The kinetics models of load and electromechanical actuator are found respectively. The relation between output speed and output power， the relation between output speed and output force， the relation between hinge position and output power， the relation between hinge position and output force are explored. The Genetic Algorithm is taken to optimize the output speed and the hinge position. The optimum match relation between the output speed and the hinge position is got. It can improve work efficiency， make space layout of the whole device optimal and make the installation space the best compact.